Understanding the dynamics of the value chain - Presutti, William D.; Mawhinney, John. (New York, NY : Business Expert Press, 2013)
The year was 1985. Michael Porter of the Harvard Business School published his business best-selling book, Competitive Advantage. It was touted at the time as'the most influential management book of the past quarter century.' In that book, Porter introduced the concept of the value chain, described as'a systematic way of examining all activities a firm performs and how they interact, (necessary) for analyzing the sources of competitive advantage.' Looking back, the most significant and lasting contribution of Porter's value chain was the notion of interrelationships among a firm's many activities. It is the idea of'linkages,' as he called them, which was the real breakthrough in management thinking. The linkages could be either horizontal among the activities inside the firm or vertical with constituents outside the firm including suppliers and customers. It was the firm and its outside constituencies and their respective value chains that formed what he called the value system in which all organizations operate.
Includes bibliographical references (p. 121-124) and index.
Keywords: Competition; Value added